Hepatic Portal Venous Gas (HPVG) after Ingestion of Chlorine Bleach: A Transient Phenomenon - Francesco M. Arico; Francesco Buemi; Pietro Pitrone; Claudio Giardina; Renato Trimarchi; Flavia Borruto; Sarah Doria; Cristina Turiaco; Simona Caloggero (Diagnostics, 2023)
We present a case involving a 32-year-old man who ingested chlorine bleach with self-defeating intent. The ingestion of bleach can lead to a wide range of consequences, from mild mucosal burns to severe complications, rarely resulting in death. This case highlights the association between chlorine bleach ingestion and the development of hepatic portal venous gas (HPVG), a radiological finding traditionally thought to carry poor prognoses. The HPVG in this case resolved spontaneously within 24 h with conservative management, indicating its transient nature. The exact pathophysiological mechanisms responsible for HPVG after the ingestion of toxic substances .remain only partially understood. One hypothesis suggests that extensive damage to the gastrointestinal wall caused by caustic agent may allow enteric gas to enter the portal system. While HPVG after toxic ingestion is often transient, its consequences and potential risks should be carefully considered. Hyperbaric oxygen therapy is suggested in cases with neurological symptoms. In conclusion, HPVG is not a specific disease but rather a manifestation of various underlying factors, and its development in the context of chlorine bleach ingestion represents an additional insight to its understanding. It can be associated with severe medical conditions, but it is also found in less severe cases that can be managed conservatively.